2021
DOI: 10.1038/s41598-021-88336-y
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically defined environments direct cell division rate and subcellular YAP localization in single mouse embryonic stem cells

Abstract: Mechanotransduction via yes-associated protein (YAP) is a central mechanism for decision-making in mouse embryonic stem cells (mESCs). Nuclear localization of YAP is tightly connected to pluripotency and increases the cell division rate (CDR). How the geometry of the extracellular environment influences mechanotransduction, thereby YAP localization, and decision-making of single isolated mESCs is largely unknown. To investigate this relation, we produced well-defined 2D and 2.5D microenvironments and monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…The most significant limitation of 2PP is the relatively long printing time hindering the upscaling of the technology ( Moroni et al, 2018 ). Multiple polymeric, hydrogel or composite materials were employed in combination with 2PP to fabricate micro- and nano-patterns as well as 3D structures for in vitro cellular studies involving neuroblastoma, glioblastoma, prostate cancer, murine cerebellar granule, chondrocytes, macrophages, neuronal and stem cells ( Marino et al, 2013 ; Accardo et al, 2017 , 2018 ; Turunen et al, 2017 ; Maciulaitis et al, 2019 ; Fendler et al, 2019 ; Babi et al, 2021 ; Bertels et al, 2021 ; Maciulaitis et al, 2021 ; Nouri-Goushki et al, 2021 ; Akolawala et al, 2022 ; Costa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most significant limitation of 2PP is the relatively long printing time hindering the upscaling of the technology ( Moroni et al, 2018 ). Multiple polymeric, hydrogel or composite materials were employed in combination with 2PP to fabricate micro- and nano-patterns as well as 3D structures for in vitro cellular studies involving neuroblastoma, glioblastoma, prostate cancer, murine cerebellar granule, chondrocytes, macrophages, neuronal and stem cells ( Marino et al, 2013 ; Accardo et al, 2017 , 2018 ; Turunen et al, 2017 ; Maciulaitis et al, 2019 ; Fendler et al, 2019 ; Babi et al, 2021 ; Bertels et al, 2021 ; Maciulaitis et al, 2021 ; Nouri-Goushki et al, 2021 ; Akolawala et al, 2022 ; Costa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in YAP nuclear localization was highly correlated with the increase in myofibroblast activation indicating that YAP may be driving this change. Previous studies have shown that YAP nuclear localization is tied to fibroblast activation and proliferation [32][33][34] . Blockage of YAP activity with verteporfin reduced myofibroblast activation on 25 kPa gels and on plastic.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in YAP nuclear localization was highly correlated with the increase in myofibroblast activation indicating that YAP may be driving this change. Previous studies have shown that YAP nuclear localization is tied to fibroblast activation and proliferation 32 34 . Blockage of YAP activity with verteporfin reduced myofibroblast activation on 25 kPa gels and on plastic.…”
Section: Discussionmentioning
confidence: 99%